GAMBARAN KOMUNIKASI ORGANISASI DI PT. X - Indira Miranti Ayuningtyas; Rayini Dahesihsari (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2015)
Companies usually hire consultants to gain professional and methodologically expertise for a particular field. PT. X is one among consulting firms that provides services in the field of psychology. PT. X usually provides short time projects which fulfill the needs of customers. It was evident that there is a bottleneck in the workflow, involving lack of well coordinated schedules, miscommunication between employees, and unclear information about projects. It was assumed that the root of the problem is ineffective communication. This study aims to describe organizational communication in PT. X. It used a qualitative approach involving four respondents who were selected through the maximum variation technique. Two respondents are corporate members and two respondents are associated partners. Data obtained from interviews analysed by content analysis. The results showed that superiors and subordinates often communicate directly, information flow from various parties and tends to run in an informal, where information is not given in written. The channel of communication varies depending on who is delivering the messages. Corporate members coordinate with each other by exchanging information related to the task mostly through informal meetings. Media communication frequently used is the online media. With this informal communication, information on the organization is still considered adequate for corporate members while seems to be inadequate for associated partners.